Satellite data for agricultural index insurance - Woerd, Joost van der (Technical Centre for Agricultural and Rural Cooperation, 2018)
How can we ensure that drought is no longer an outright disaster to smallholder farmers in Africa, but instead a manageable risk? With low-cost satellite-based index insurance products that monitor climatic conditions in near real-time and automatically trigger a pay-out when conditions are below normal. This helps farmers secure necessary credit for inputs, recover faster from bad seasons and sustainably improve their livelihoods.